Structural, optical, and magnetic properties of NiMoO4 nanorods prepared by microwave sintering - Moura, Ana Paula de [UNESP]; Oliveira, Larissa Helena de [UNESP]; Rosa, Ieda Lucia Viana; Xavier, Camila Soares [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Li, Máximo Siu; La Porta, Felipe de Almeida [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley, 2015)
We report on the structural, optical, and magnetic properties of α,β-NiMoO4 nanorods synthesized by annealing the NiMoO4:nH2O precursor at 600°C for 10 minutes in a domestic microwave. The crystalline structure properties of α,β-NiMoO4 were investigated using X-ray diffraction (XRD), Fourier transform infrared (FTIR), and Raman (FT-Raman) spectroscopies. The particle morphologies and size distributions were identified by field emission microscopy (FE-SEM). Experimental data were obtained by magnetization measurements for different applied magnetic fields. Optical properties were analyzed by ultraviolet-visible (UV-vis) and photoluminescence (PL) measurements. Our results revealed that the oxygen atoms occupy different positions and are very disturbed in the lattice and exhibit a particular characteristic related to differences in the length of the chemical bonds (Ni-O and Mo-O) of the cluster structure or defect densities in the crystalline α,β-NiMoO4 nanorods, which are the key to a deeper understanding of the exploitable physical and chemical properties in this study.